Triptorelin for the treatment of endometriosis. (June 2014) - Leone Roberti Maggiore, Umberto; Scala, Carolina; Remorgida, Valentino; Venturini, Pier Luigi; Del Deo, Fabio; Torella, Marco; Colacurci, Nicola; Salvatore, Stefano; Ferrari, Stefano; Papaleo, Enrico; Candiani, Massimo; Ferrero, Simone
Abstract : Introduction: Over the past 30 years, gonadotropin-releasing hormone agonists (GnRH-a) have been used to induce a hypoestrogenic status in women with endometriosis with the aim to cause an improvement in pain symptoms similar to that observed after menopause.Triptorelin is one of the most commonly used GnRH-a. Areas covered: This review offers an explanation of the mechanism of action, of the pharmacokinetics and pharmacodynamics of triptorelin and gives the readers a complete overview of the studies on the clinical efficacy, tolerability and safety of this agent in patients with endometriosis. Expert opinion: The studies reviewed in the current manuscript demonstrate the efficacy of triptorelin in improving pain symptoms caused by endometriosis. Further, this effect is confirmed by the reduction in the volume of the endometriotic nodules during treatment. Future research should evaluate whether the pre-operative administration of triptorelin prior to surgical excision of endometriomas may be useful in preserving the ovarian reserve.